PRESTASI BELAJAR SISWA DITINJAU DARI DUKUNGAN SOSIAL ORANG TUA - Sri Anjariah (Jurnal Psikologi, 2006)
One hundred and thirty eight students grade eleventh participated on this research. It was expected that the students' academic performance was influenced by their parents* social supports Those supports consisted of providing relevant information, emotional encouragement, providing accurate evaluation, and providing learning facilities. It was found that die product moment correlation score was .290, p < .01. Indeed, this research has underlined the crucial parental influence on children's academic performance.